p-6=3(p-4)

Simple and best practice solution for p-6=3(p-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p-6=3(p-4) equation:


Simplifying
p + -6 = 3(p + -4)

Reorder the terms:
-6 + p = 3(p + -4)

Reorder the terms:
-6 + p = 3(-4 + p)
-6 + p = (-4 * 3 + p * 3)
-6 + p = (-12 + 3p)

Solving
-6 + p = -12 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
-6 + p + -3p = -12 + 3p + -3p

Combine like terms: p + -3p = -2p
-6 + -2p = -12 + 3p + -3p

Combine like terms: 3p + -3p = 0
-6 + -2p = -12 + 0
-6 + -2p = -12

Add '6' to each side of the equation.
-6 + 6 + -2p = -12 + 6

Combine like terms: -6 + 6 = 0
0 + -2p = -12 + 6
-2p = -12 + 6

Combine like terms: -12 + 6 = -6
-2p = -6

Divide each side by '-2'.
p = 3

Simplifying
p = 3

See similar equations:

| 8+6(t+2)=32 | | 8-6m=26 | | 8m-7(3-5m)=280 | | -12-2k=-2(k+4) | | x+135+20=x+35 | | 3(x+6)=221 | | x+40+2x-10=180 | | 1.4b+10=18 | | 34+8m=6(3m+1)-3m | | -4(2x-1)=2(3x+2)-14x | | 2a-6+5a=3-a+7 | | 3+7(-3n+6)=-4n-6 | | -6(z-2)=3 | | 17+(-3x)=14 | | 2x-10-7x=3(x-6) | | 6(7-6n)=114 | | 7(5x-4)=5+2x | | n^2+(-3)(4)=28 | | 17+(-3)=14 | | 5+X=-36 | | 2y+7=35 | | h=16t^2+52t+16 | | 4.95+11.95=64.70 | | 40+2m=-8(m+5) | | x+74+36=77 | | 5(x-3)-4(x-3)=3(x-1) | | 2x^4-10x^2+5=0 | | 10t^2-17t+6=0 | | -4w+8=-8(w+3) | | 0.23*50=1*x | | -4z=126 | | 3x-10(x+2)=1.22-7x |

Equations solver categories